STUDY ON INHERITANCE OF BLAST RESISTANCE IN RICE (Oryza sativa L.) - CH. SREELAKSHMI; P. RAMESH BABU (The Journal of Research ANGRAU, 2023)
The study on generation mean analysis was conducted with six selected crosses of rice which were subjected to blast disease in uniform blast disease nursery. The material consisting of all the six generations (P1, P1, F1, F2, BC1 and BC2 ) revealed the role of digenic interactions in the inheritance of blast disease which was taken up at Agricultural Research Station, Nellore during 2017-18 rabi seson. In F1 generation, all the hybrid combinations showed resistant reaction for blast. In case of F2 generation, duplicate type of epistasis was observed in the cross combinations viz., RNR 2465 x NLR 145, BPT 5204 x IR 64, BPT 5204 x NLR 34449 and RNR 2465 x IR 64 indicating that the involvement of digenic gene action and selection for this trait will be taken up in the later generations when desirable transgressive segregants are available. The crosses BPT 5204 x IR 36 and WGL 48684 x IR 36 exhibited 3:1 type of phenotypic ratio (R:S) indicating that single dominant gene governs the resistant reaction in these crosses.